ANALISIS EFEK SAMPING PEMAKAIAN KONTRASEPSI SUNTIK DEPO PROGESTIN PADA IBU DI PUSKESMAS MUTIARA BARAT TAHUN 2021 - Salamah; Zaitun; Indah Nazira (Nusantara Hasana Journal, 2021)
Injectable contraception has both good and bad effects for users, the good effects include being very effective and having a long-term pregnancy prevention effect, no effect on marital relations, does not contain estrogen so it does not have a serious impact on heart disease and blood clotting disorders, does not affect breast milk , preventing endometrial cancer and ectopic pregnancy, reducing the incidence of benign breast disease, preventing some pelvic inflammatory diseases, reducing crescent anemia crises, and few side effects. Other impacts include disruption of menstrual patterns, delays in returning to fertility (disturbances of menstrual problems), weight gain, emotional instability, depression, and does not guarantee protection against sexually transmitted infections (Saroha Pinem, 2014). This study used an analytic survey design with a cross sectional design. The population in this study were all 723 depo progestin injection contraceptive acceptors in 2021 with a total sample of 61 respondents. This research was conducted at the Mutiara Barat Health Center in October 2021. This research used primary data in the form of direct data from respondents based on a questionnaire and secondary data from the medical records of the Mutiara Barat Health Center and library book references and other supports. Data were analyzed using bivariate analysis, namely the chi-square test at a significance level of 95% (ρ<0.05) using SPSS version 25 for windows. The conclusion obtained is that there is a relationship between menstrual disorders, weight gain, vaginal discharge, and headaches with the side effects of birth control depo progestin injections. Suggestions for Health Services, especially the Community Health Centers, to be able to improve counseling about family planning, especially Sfor family planning so that it can provide a clear picture of the types of family planning and the side effects caused by the contraceptives used, so that it will not impact drop out in contraceptive use due to the acceptors' ignorance about side effects of the contraceptives used.